2001
DOI: 10.1590/s0100-879x2001000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin and fluoxetine on blood glucose regulation in two decapod species

Abstract: One of the best known crustacean hormones is the crustacean hyperglycemic hormone (CHH). However, the mechanisms involved in hormone release in these animals are poorly understood, and thus constitute the central objective of the present study. Different groups of crustaceans belonging to diverse taxa (Chasmagnathus granulata, a grapsid crab and Orconectes limosus, an astacid) were injected with serotonin, fluoxetine, or a mixture of both, and glycemic values (C. granulata and O. limosus) and CHH levels (O. li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 22 publications
(17 reference statements)
5
19
0
Order By: Relevance
“…Moreover, cHH release increases as a function of 5-HT concentration in vivo, and a similar trend was reported in an in vitro system by Escamilla-Chimal et al (2002). In O. limosus, injection of 5-HT caused a significant increase of the circulating level of cHH (Santos et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, cHH release increases as a function of 5-HT concentration in vivo, and a similar trend was reported in an in vitro system by Escamilla-Chimal et al (2002). In O. limosus, injection of 5-HT caused a significant increase of the circulating level of cHH (Santos et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Serotonin (5-HT; 5-hydroxytryptamine) is well known as a neurotransmitter in crustaceans on several grounds, and its levels have been measured in the nervous system and hemolymph of various crustacean species (Elofsson et al, 1982;Laxmyr, 1984;Kulkarni and Fingerman, 1992), thus suggesting a possible role as a neurohormone (Rodrigues-Soza et al, 1997). Serotonin has long been known to have a potent hyperglycemic effect in several crustacean species (Bauchau and Mengeot, 1966;Keller and Beyer, 1968;Lee et al, 2000;Lorenzon et al, 1999Lorenzon et al, , 2004aSantos et al, 2001). Lee et al (2001) confirmed the role of 5-HT in mediating the release of cHH.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In aquatic animals, hyperglycaemia is a typical stress response to harmful physical and chemical environmental changes, including hypoxia and exposure to air during commercial transport (Spicer et al, 1990;Zou et al, 1996;Kuo and Yang, 1999;Morris and Olivier, 1999;Durand et al, 2000;Speed et al, 2001). Hyperglycaemia has been associated with increased circulating CHH titres (Lorenzon et al, 1997;Lorenzon et al, 2002;Durand et al, 2000;Santos et al, 2001), and has been used as an index to assess CHH activity and environmental stress (Webster, 1996;Bergmann et al, 2001;Toullec et al, 2002). Accordingly, in P. clarkii in the present study, acoustic stress led to a significant increase (P<0.01) in haemolymph glucose levels.…”
Section: Discussionmentioning
confidence: 50%